THE ART CREATIVE PROCESS OF INDONESIAN CHILDREN IN THE STUDENT’S NATIONAL COLLECTIVE PAINTING COMPETITION IN 2018 - Arisianto, Arisianto; Triyanto, Triyanto; Syarif, Muh. Ibnan (Catharsis, 2019)
Creative process is a process on how an artwork created through a physiological and psychological process. All of the art creators, including children, have their own different way to create artworks. This research was held to analyze an art creative process of Indonesian Children in the Student’s National Collective Painting Competition in 2018. This research was held in Indonesian National Gallery at Jalan Medan Merdeka Timur No. 14, Gambir, RT.6/RW.1, Gambir, Central Jakarta. The approach of this research is cultural approach with phenomenology research design. The technique of data collection was observation, interview, and documentation. The data validity was done through; a) reflection through an experience observed; b) asking an opinion from colleagues or other researchers; c) rational analysis by beating out whether a phenomenological description from the whole subjective meanings of are logic or not. The data analysis was done through four steps, the first is data grouping, second is reduction and elimination of data. Third, giving the occurring data from the reduction stage and then named. Fourth, the data identification stage. The results show that the painting creative process of children shows the highest creativity process, it is a conclusion from the whole creative process that are achieved from painting. The art competition should not only see only from the result, but also from the process so the children are not trapped in aesthetic matter, but process is also becomes a determining part in building creative ideas. The museum institution, like Indonesian National Gallery should see more on the children’s honesty in painting, therefore type haptik painting is still can be found in the collective painting competition.